(untitled) (Advances in Civil and Architectural Engineering, 2023)
Rice husk ash (RHA), owing to its pozzolanic properties and wide abundance, is an additive that can be used as an alternative to cement to improve a variety of soils. Damping and shear modulus are two important soil dynamic parameters used to predict soil behaviour under dynamic loading. Therefore, in this study, materials were prepared and their specifications were determined. A cyclic triaxial device was used to determine the dynamic parameters (stress control). Subsequently, the results related to shear modulus and damping calculated for pure sand before and after stabilisation were analysed according to different percentages of stabilisers for two frequencies of 0.5 and 1 Hz. The results revealed the effect of different frequencies on the damping of pure sand, which differed for stabilised sand. In all stabilised specimens, the shear modulus decreased with increasing frequency. Additionally, the damping decreased with increasing frequency in the stabilised samples. The shear modulus increases with the increase in the amount of stabilisers. The results also showed the positive effect of partially replacing cement with RHA.